Analisis Bibliometrik Tren penelitian Green Library yang terindeks Google Scholar tahun 2020-2025 - Rohmah, Maftuhatur (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze research trends on green libraries published in Google Scholar–indexed journals during the period 2020–2025 using bibliometric methods. Data were collected through Publish or Perish (PoP) and analyzed with VOSviewer to map author collaboration and keyword relationships. A total of 94 relevant journal articles were examined. The findings reveal that “green library” is the most central theme, closely associated with keywords such as “sustainability,” “eco-friendly,” and “environmental literacy.” The co-occurrence analysis identified 179 keywords grouped into 21 thematic clusters. Meanwhile, the co-authorship analysis shows 25 authors connected within collaborative networks, with significant growth in collaboration during 2024–2025. These results indicate a research shift from general conceptual discussions toward more specific topics, including international initiatives, standards, and challenges in implementing green libraries. This study contributes to the development of environmentally sustainable library policies and enriches the academic discourse on sustainability in librarianship.